Integrated defective production model for impatient customers with price dependent demand under the effect of learning. (1st January 2014) - Shastri, Aditya; Singh, S.R.; Gupta, Shalley
In this paper, a three-echelon supply chain model has been explored, comprising of a supplier, a producer and a retailer where demand rate is functionally related to the selling price. In this study, it is assumed that customers are impatient in nature so shortages occur at the end of retailer. Production process assumes to be imperfect and defective items reworked and available for sale as good ones. Number of defective items present in supplier end follows the learning curve. The model has been explored numerically as well, an optimal solution has been obtained and the sensitivity of that solution has also been checked with respect to various system parameters. The final outcome shows that the model is not only stable but also economically feasible.